2019
DOI: 10.1080/21691401.2019.1632322
|View full text |Cite
|
Sign up to set email alerts
|

OB-RGRP regulates the phosphorylation of JAK2 and STAT3 in primary rat adipocytes

Abstract: This study aimed to explore the role of obestatin R gene-related protein (OB-RGRP) in autocrine signal transduction of adipocytes. Primary rat adipocytes were isolated and verified by microscopic observation and oil red O staining. OB-RGRP expression vector and OB-RGRP siRNA (si-OB-RGRP) were constructed and transfected into adipocytes. Adipocytes were then divided into five groups: (1) Control; (2) Vector (empty expression vector); (3) OB-RGRP (OB-RGRP expression vector); (4) si-OB-RGRP NC (si-OB-RGRP negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In cancer cells, the molecular signaling processes were always aberrantly up/downregulated and/or functionally modified ( Li et al, 2019 ) ( Yang et al, 2020a ; Barrett and Puré, 2020 ). As a result of conflicting reports on the impact of LEPROT on downstream signaling and cancer progression, and the lack of investigation on it, a bioinformatic analysis on LEPROT among multiple cancer types was, therefore, conducted for a broader understanding of the roles of LEPROT in cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer cells, the molecular signaling processes were always aberrantly up/downregulated and/or functionally modified ( Li et al, 2019 ) ( Yang et al, 2020a ; Barrett and Puré, 2020 ). As a result of conflicting reports on the impact of LEPROT on downstream signaling and cancer progression, and the lack of investigation on it, a bioinformatic analysis on LEPROT among multiple cancer types was, therefore, conducted for a broader understanding of the roles of LEPROT in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin exerts its biological action majorly through binding to and activating the leptin receptors (LEPR) ( Garofalo and Surmacz, 2006 ; Ghasemi et al, 2019 ), and the gene encoding LEPR overlapping transcript (LEPROT), which is shown to negatively regulate leptin signaling by reducing expressions of LEPR on the cell membrane, is considered as an anticancer factor in cancer progression. However, a more recent study paradoxically reported that LEPROT could activate the JAK/STAT signaling ( Li et al, 2019 ), which may theoretically facilitate cancer development ( Mullen and Gonzalez-Perez, 2016 ). Therefore, the role of LEPROT in tumors may not be limited to the previous cognition that it only serves as a negative regulator of leptin signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that LEPROT could negatively regulate the cell surface expression of LEPR and the silencing LEPROT expression in the mouse hypothalamic arcuate nucleus prevented the development of high-fat-diet-induced obesity ( 19 ). In contrast, LEPROT was found to activate the JAK/STAT pathway and may facilitate cancer development ( 20 ). A recent study identified an aberrant expression of LEPROT in 78.9% cancers compared with corresponding normal tissues ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In cancer cells, the molecular signaling processes were always aberrantly up/downregulated and/or functionally modified (Li et al, 2019) (Yang et al, 2020a;Barrett and Puré, 2020). As a result of conflicting reports on the impact of LEPROT on downstream signaling and cancer progression, and the lack of investigation on it, a bioinformatic analysis on LEPROT among multiple cancer types was, therefore, conducted for a broader understanding of the roles of LEPROT in cancers.…”
Section: Discussionmentioning
confidence: 99%